Th e quality of services in the electronic environment and new services - O. V. Serova (Библиосфера)
Implementing new technologies in library practice allows automation all stages of users’ work both in the library and in the remote access. Remote users can get library services in a large measure as the readers that work within the library. One of the problems here is forming information re-quest. The results of investigation, started in the State Library of Russia in 2005, of the satisfaction degree of information and library services of readers using electronic catalog are  presented; possibilities of new services being implemented in libraries are described.